Is the Implementation of Problem-Based Learning Appropriate? A Literature Review on Accounting Learning - Wilda Auwalina Istigfarin; Endang Sri Andayani (Dinamika Pendidikan, 2023)
The objective of this study is to examine the development of research results on the implementation of Problem-Based Learning (PBL) in accounting learning in Indonesia within a 10-year period (2012 – 2022). The research was conducted using the Systematic Literature Review (SLR) method. A review was carried out on 54 PBL articles in the field of accounting education in Sinta 1-6 accredited journals. Research results showed the following findings, there were 54 published articles on PBL in the accounting field from 2012 to 2022, and most articles were published in 2017-2018. The most popular variants on the PBL research method in the accounting field employed Classroom Action Research (41%), followed by experimental research (33%). Most of the research objects involved vocational high schools, universities, and senior high schools. Of the 54 articles that were examined, only 18 articles presented the learning syntax in accordance with the PBL terms from Howard Barrows. Another 12 articles did not follow the PBL terms, but did present problems in learning. However, the utilized problems were not in accordance with the characteristics of problems in PBL, which involve real, unexpected, and unplanned (unstructured) problems. This is presumably because the researchers (1) do not fully understand the features of PBL, or (2) have problems formulating problems in the accounting field that are in accordance with the demands of PBL.